Sistem Pendeteksi Kebocoran Gas LPG Menggunakan Metode Fuzzy yang Diimplementasikan dengan Real Time Operating System (RTOS) - Lavanna Indanus Ramadhan; Dahnial Syauqy; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
LPG is an alternative fuel that people use for daily purposes, in addition, LPG has cheaper prices and is also easier to use. However, LPG is flammable and has heavier characteristics that are bigger than air, making it difficult to detect the gas in case of leakage. Based on the problem, a system capable of detecting leakage of LPG gas and its leakage level based on gas content and temperature on LPG. In this research there are 2 sensors that are gas module MQ-6 and LM35 temperature sensor connected with arduino uno microcontroller and can be used as a feature to classify gas condition using fuzzy sugeno method. The output of the system is displayed using the LCD and marked with a buzzer sound. In arduino uno embedded RTOS that served as scheduling task on the system. The RTOS used is already provided in the Arduino Uno library ie FreeRTOS. From the test results, the system can determine the various conditions on the gas leak with accuracy reaches 100%. Scheduling tasks performed in accordance with the priorities made. The average system execution time using RTOS is 1.8976 ms, while the system without RTOS is 1,7304 ms. System with RTOS takes longer time, because in system there is take-and-give semaphore function which need execution time for Â± 0,05 ms.